A critical review of two translated isiXhosa children's texts. Issue 4 (2nd October 2017) - Madolo, Yolisa
Abstract: Translation of children's literature requires more than basic translation skills. A translator needs to be an artist and a writer to be a successful translator of children's literature. Functionalist theories like Nida's Functional Equivalence theory and Skopos theory advocate that translation needs to focus more on the target language readership. At the same time, it is through the brief emphasised by the Skopos theory that the target audience is understood – their age, level of education, etc. The aim of this presentation is to critically review two translated isiXhosa children's books, looking at their target reader friendliness. The findings are that most parts of the text are target reader-oriented, though translators at times seem loyal to the source language.